Solving Nonlinear Partial Differential Equations by the sn-ns Method - Alvaro H. Salas (Abstract and Applied Analysis)
We present the application of the sn-ns method to solve nonlinear partial differential equations. We show that the well-known tanh-coth method is a particular case of the sn-ns method.